Temperature Requirements of Some Common Forensically Important Blow and Flesh Flies (Diptera) under Laboratory Conditions - AH Shiravi; R Mostafavi; K Akbarzadeh; MA Oshaghi (Tehran University of Medical Sciences, 2011)
Background: The aim of his study was to determine development time and thermal requirements of three myiasis flies including Chrysomya albiceps, Lucilia sericata, and Sarcophaga sp. Methods: Rate of development (ROD) and accumulated degree day (ADD) of three important forensic flies in Iran, Chrysomya albiceps, Lucilia sericata, and Sarcophaga sp. by rearing individuals under a single constant temperature (28° C) was calculated using specific formula for four developmental events including egg hatching, larval stages, pupation, and eclosion. Results: Rates of development decreased step by step as the flies grew from egg to larvae and then to adult stage; however, this rate was bigger for blowflies (C. albiceps and L. sericata) in comparison with the flesh fly Sarcophaga sp. Egg hatching, larval stages, and pupation took about one fourth and half of the time of the total pre-adult development time for all of the three species. In general, the flesh fly Sarcophaga sp. required more heat for development than the blowflies. The thermal constants (K) were 130-195, 148-222, and 221-323 degree-days (DD) for egg hatching to adult stages of C. albiceps, L. sericata, and Sarcophaga sp., respectively. Conclusion: This is the first report on thermal requirement of three forensic flies in Iran. The data of this study provide preliminary information for forensic entomologist to establish PMI in the area of study.